Study of the Oil Constituents Extracted from Leaf, Flower and Gramineous Stipes of Vitex Pseudo-negundo - TAYEBEE, REZA; FILEHKESH, E.; AMANI, VAHID (Asian Journal of Chemistry, 2010)
According to experimental findings, limonene (28.8%), myrcene (17.06%) and caryophyllene oxide (27.5%) are the major constituents of oil extracted from leaf, flower and gramineous stipes of Vitex pseudo-negundo, respectively which was collected from Sabzevar province at the east of Iran in August 2004.